2014
DOI: 10.1063/1.4876750
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon coupling enhanced by the FeSe/SrTiO3 interface

Abstract: The electronic structure, phonon dispersions, and electron-phonon (EP) coupling in Fe2Se2/SrTiO3 (FeSe/STO) thinnest films are studied based on the first-principles calculations. It is found that the FeSe/STO interface with lattice strain leads to a change of band structures and a significant enhancement of the EP coupling, the latter being close related to interface-induced ferroelectric phonons coupled to electrons on the FeSe monolayer. In the FeSe/STO system, Tc of phonon-induced superconductivity is estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 19 publications
2
75
0
Order By: Relevance
“…For the same reasons, the calculated coupling strengths and widths in q space in Ref. 26 are overestimated.…”
Section: Results and Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…For the same reasons, the calculated coupling strengths and widths in q space in Ref. 26 are overestimated.…”
Section: Results and Analysismentioning
confidence: 95%
“…14 This momentum structure has been qualitatively confirmed by recent ab initio calculations for the interface e-ph coupling. 26 However, in light of the sharpness of the replica bands, the q-resolution in Ref. 26 is not in line with the sharpness of the coupling in momentum space that is necessary to explain this experiment.…”
Section: Introductionmentioning
confidence: 92%
“…Measuring high-resolution ARPES spectra, they observed that the electronic bands of the FeSe monolayer are replicated with an energy shift of 100 meV. They attribute this effect to a strong electronphonon coupling between the layer and the substrate [89]: a phonon mode, most probably an oxygen optical phonon, in SrTiO 3 couples to the FeSe electrons.…”
Section: Superconductivity In Atomically Thin Fese Layersmentioning
confidence: 99%
“…To the best of our knowledge, no sign of (π, π) magnetic order has been observed in FeSe thin films with only electron pockets. First-principle calculations for the momentumindependent phonon coupling estimate a resulting T c 1 K [60], an energy scale that may be too small to significantly lift the degeneracy, since T c ≈ 40 K in FeSe thin films.…”
Section: Microscopic Modelmentioning
confidence: 99%